Reconciliation or restoration? The ecological futures of floodplain buyout sites - Vanucchi, Jamie; Shi, Linda; Hulet, Carri (Frontiers in Climate, 2025)
What happens to floodplain buyout sites after demolition of structures? Does ecological restoration or reconciliation of the floodplain occur? By what criteria should we assess what is on the site? Under what conditions do government programs promote more ecologically dynamic land management? We explore these questions in the context of four exemplary buyout programs in the United States that implement relocation out of flood risk zones through buyouts: Austin’s Watershed Protection Department, Texas; Harris County Flood Control District, Texas; Charlotte-Mecklenburg’s Stormwater Services, North Carolina; and Washington State’s Floodplains by Design. The analysis draws on staff interviews and GIS mapping, satellite imagery for 3,416 buyout parcels spanning 2,811 acres, and selected field verification. We test a framework for assessing buyouts that includes both pre- and post-buyout considerations as indicators along a spectrum from reconciliation to restoration. Our findings show that the status of most buyout parcels is “in-waiting,” as land management practices evolve to decide on their long-term use. Federal buyout requirements prevent redevelopment, but it is local and state priorities, goals, capacities, partnerships and levels of community engagement that shape land management outcomes and long-term human-nature relations. While the reconciliation-restoration debate often pits social against ecological goals, we find that they are mutually reinforcing, and that deep community engagement yields better outcomes overall. Floodplains are high value landscapes and should be prioritized for repair. State and federal governments can help achieve greater ecological and social outcomes from buyout sites by issuing more explicit guidance, technical assistance, and funding support to achieve these aims.